File Integrity Verifier Using Digital Signature Algorithm and SHA-256 with Memory-Mapping Technique - Bañas, Joy Camagon; Mababa, Jonilo C. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The study aims to develop a specialized File Integrity Verifier system tailored for educational sectors, with a primary focus on the Philippine Society of Information Technology Educators-Central Luzon (PSITE-CL). The system will employ various advanced methods, including the Digital Signature Algorithm (DSA), Secure Hash Algorithm 256-bit (SHA-256), Memory-Mapping technique, Laravel PHP framework, and Argon2 hashing algorithm, to ensure the utmost security and effective digital file management. The ultimate goal is to guarantee accuracy and efficiency in handling confidential and critical data within these organizations. Method – This study will employ a combination of Descriptive and Research and Development (R&D) methods. By integrating descriptive research and R&D, the study will gain comprehensive insights into the current systems, technologies, and user behaviors, leading to the development of innovative solutions. Conclusion - The implementation of a file integrity verifier system offers numerous benefits, including enhanced data security, accuracy, and efficiency. By adopting this system, educational sectors can ensure the authenticity and integrity of digital documents, prevent non-repudiation of uploaded files, streamline workflows, reduce cyber-attack risks, and maintain the credibility of academic records. Furthermore, the technologies and methods that will be used in this system can overcome the limitations of traditional hash function-based approaches, addressing issues related to time consumption, resource utilization, and vulnerability to attacks. Recommendation - This study strongly recommends the adoption of the proposed system in educational sectors, with a specific focus on the PSITE-CL. Implementing this technology will significantly enhance data security measures, ensure compliance with privacy regulations, and mitigate the risks associated with unauthorized modifications to digital records. Practical Implication - The File Integrity Verifier system holds the potential to benefit not only educational sectors, and students but also regulatory bodies, future researchers, and developers.